PROSPECTS FOR USING THE STEAM APPROACH1 IN THE EDUCATIONAL PROCESS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article examines the compatibility of the Steam approach with the ability for self-learning and teamwork, and the benefits of an effective interactive learning approach. The article describes how the STEAM approach differs from the traditional type of learning and how students' thinking develops.